The effects of kappa opioid agonist RU-1205 on local field potentials and behavior in the discriminative stimulus paradigm - K. Yu. Kalitin; O. Yu. Mukha; A. A. Spasov (Фармация и фармакология (Пятигорск))
Kappa opioid receptors play a pivotal role in regulating both physiological and cognitive processes. RU-1205, a benzimidazole derivative acting as a specific kappa opioid receptor agonist, has demonstrated the capacity to modulate neuronal activity. However, the nuanced effects of RU-1205 on neuronal activity remain incompletely understood.The aim of the study was to identify and elucidate the effects of the kappa opioid agonist RU-1205 on local field potentials and behavior in the discriminative stimulus paradigm.Materials and methods. The experiments were conducted in male rats weighing 260–280 g. The animals were surgically implanted with cortical electrodes (F — frontal, O — occipital, P — parietal) as well as deep electrodes in specific brain regions, including the medial prefrontal cortex (mPFC), hippocampus (Hipp), nucleus accumbens (NAc), ventral tegmental area (VTA) and amygdala (Amy). LFP signals were obtained and analyzed after the administration of the compound RU-1205 (350 μg/5 μl intracerebroventricular injections) using spectral and coherence analysis methods. Drug discrimination paradigm was employed to evaluate the similarity of the compound RU-1205 to the selective kappa opioid receptor agonist U-50488 and the p38 MAPK inhibitor SB203580 (including in combination with the opioid receptor blocker naloxone).Results. Electrophysiological changes observed include an increase in power of theta frequencies (4–8 Hz) in F, P and mPFC leads, along with a reduced power of delta frequencies (0.5–4 Hz) in O and Hipp leads, and a suppression of gamma activity (30–50 Hz) in F and mPFC leads, all with statistical significance (p <0.05). Post-administration of RU-1205 resulted in a decreased coherence between pairs of electrodes: P–O, P–F, F–O, and mPFC–Hipp (all p <0.05). It was found that the compound RU-1205 is similar to U-50488 and does not exhibit p38 inhibitory activity in the discriminative stimulus paradigm.Conclusion. Compared to the selective kappa-opioid agonist U-50488, the compound RU-1205 induces less significant changes in LFP activity without electrophysiological and behavioral signs of beta-arrestin pathway activation. The overall data suggest that RU-1205 is a functionally selective agonist of kappa-opioid receptors.